PENERIMAAN KHALAYAK DESA PONGGOL MAGELANGTERHADAP PROGRAM GENDU-GENDU ROSO GRABAGTV - Yulita, Reni Diyah; Murfianti, Fitri (Seni Media Rekam ISI Surakarta, 2012)
GrabagTV is one of community televisions that has been operated in Indonesia.It wasestablished in 2004 in District Grabag, Magelang regency, Central Java. Grabag TV is noncommercial television. One of programs that aired is Gendu-Gendu Roso.This program is aninteractive dialogue aimed as a space to accommodate the aspirations of the people Grabag.This problem is then focused on how the public acceptance of the program Gendu-Gendu Rosoas a medium channeling the aspirations of the people in accordance with the goals and ideals ofIndonesia broadcasters.The purpose of this study is how the reader understand on how thepublic acceptance of the program being broadcasted on television community and the factorsthat affect the acceptance of the audience. This thesis using qualitative methods and theapproach used is reception analysis.This approach is used in order to determine how audiencesreceive the contents of the messages conveyed by the media viewed from a variety ofcontextual factors that influence.Audience acceptance will be obtained by a long process thatbecame valuable experience within the public and shaping the mindset and worldview different.The results of this study show that community acceptance of Gendu Gendu Roso in defendingfreedom of speech in the category dominant reception where the community agreed that theevent was able to become the voice of the container,as well as public acceptance of the use ofsetting events are also included in the reception dominant. While the acceptance of theaudience to the information included in the reception is dominant and negotiated.The lastdiscussion on the use of regional languages in the event showed that the acceptance of theaudience entered the reception is dominant,negotiated and oppositional.For people who fallinto the category of oppositional means that the use of the local language cannot be receivedwell.Public acceptance of the programs shown on television was not the same community.It isinfluenced by various factors in daily life such as social background, occupation, age, sex andneighborhood audiences.Keywords: Community television, audiences positioning, and Grabag TV